The perceptions of Likas people towards the peaceful assembly / Siti Salwa Ismail and Nurul Hidayah Zainal - Ismail, Siti Salwa; Zainal, Nurul Hidayah (2016)
Assembly is one of the ways thai the public may use to voice out their wants. Peaceful Assembly Act (2012) is the act that the Malaysian Government uses in order to ensure that the peaceful and harmonious of the country can be maintained. Thus the level of knowledge of the public towards the existence of the act itself is an important part. Likas have been targeted to be our study area. We have chosen a preliminary study to conduct this research.